Rhinogobius maculagenys, A new species of freshwater goby (Teleostei: Gobiidae) from Hunan, China - Wu, Qianqian; Deng, Xuejian; Wang, Yanjie; Liu, Yong (Zootaxa, 2018)
A new freshwater goby, Rhinogobius maculagenys sp. nov., was collected from Hunan Province in Southern China. This species can be distinguished from all congeners by a combination of the following features: first dorsal fin with 6 spines; second dorsal fin with a single spine and 7–9 segmented rays; anal fin with a single spine and 6–8 segmented rays; pectoral fin with 16 segmented rays; 32–34 longitudinal scales; 9–13 transverse scales; 11+16=27 vertebrae; pore ω1 missing; head and body yellowish brown; cheek and opercle yellowish brown with over 30 small orange spots, branchiostegal membrane yellow with over 10 small orange spots in males and white and spotless in females; first dorsal fin trapezoidal in males and nearly semicircular in females, with large bright blue blotch in front of second spine; spines 4 and 5 longest, rear tip extending to base of second branched ray of second dorsal fin in males when adpressed, but just reaching or not reaching anterior margin of second dorsal fin in females; caudal fin with 5–6 vertical rows of brown spots; flank with several longitudinal rows of blackish-brown spots; and belly pale white.